Waste Management Biotechnology for Alkaline Protease Production and Optimization - Thanoon, Raid D.; Rubaaini, Subramaniam; Mahmood, Mahmood H.; Munem, Osama A.; Makky, Essam A.; M. M., Yusoff (Universiti Malaysia Pahang, 2017)
Environmental pollution is one of the major issues in either well developed or in developing countries. Pollution can also come from animal wastes such as livestock, wastewater and feed that have been wasted. This type of circumstances occurs when there are abundant of waste generated in animal farms in certain area that is difficult to be disposed. For example, the fish residues such as fish fin, viscera, and scales can be one of the sources of contamination that can be the major problem. Moreover, chicken feather (CF) is widely disposed that results in environmental pollution as it cannot be solved with ease. Hence both fish fin (FF) and CF can be utilized to produce alkaline protease (AP) enzyme by using microbial fermentation power. Protein from each sample was extracted and determined. Then, the extracted protein from both wastes was employed in the production media together with bacterial suspension which was incubated. Next, alkaline protease assay was carried out to test for presence of alkaline protease in the samples. Optimization parameters controlling alkaline protease productivity were screened and determined. The optimum pH of CF and FF was 9.0, the optimum temperatures recorded at 28 and 40°C for CF and FF respectively, the production incubation periods were 6 and 10 days for CF and FF respectively. While, galactose and glucose exhibited the optimum carbon sources for CF and FF respectively from one hand, and the optimum nitrogen sources recorded to be ammonium chloride and beef extract for CF and FF respectively from the other hand.